2000
DOI: 10.1029/00eo00152
|View full text |Cite
|
Sign up to set email alerts
|

Tectono‐magmatic processes investigated at deep‐water flanks of Hawaiian volcanoes

Abstract: Hawaiian volcanoes are exceptional examples of intraplate hotspot volcanism. Hotspot volcanoes, which frequently host large eruptions and related earthquakes, flank‐failure landslides, and associated tsunamis, can present severe hazards to populated regions. Many studies have focused on subaerial parts of Hawaiian volcanoes, but the deep‐water flanks of the edifices, which can reach 5700 m below sea level, remain poorly understood because they are so inaccessible. In 1998 a collaborative program between Japan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Such interbedding was also observed at nearby ODP site 1223A (Figures 1 and 6; Stephen, Kasahara, et al, 2003). The limited scatter between the other pelagic velocity profiles may be caused by a lesser degree of volcanic interbedding, which has been found in the uppermost sediments surrounding the Hawaiian islands both on and off the Swell (Naka et al, 2000(Naka et al, , 2002 and has been identified in sediments over 500 km from the islands (Rehm & Halbach, 1982). We assumed linear velocity-depth gradients for both types of sediments, although many studies have found nonlinear concave down velocity-depth relationships (e.g., Hamilton, 1979;Ruan et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Such interbedding was also observed at nearby ODP site 1223A (Figures 1 and 6; Stephen, Kasahara, et al, 2003). The limited scatter between the other pelagic velocity profiles may be caused by a lesser degree of volcanic interbedding, which has been found in the uppermost sediments surrounding the Hawaiian islands both on and off the Swell (Naka et al, 2000(Naka et al, , 2002 and has been identified in sediments over 500 km from the islands (Rehm & Halbach, 1982). We assumed linear velocity-depth gradients for both types of sediments, although many studies have found nonlinear concave down velocity-depth relationships (e.g., Hamilton, 1979;Ruan et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Crumpler et al (1996) suggest the blocks might represent slide material derived from the volcano flank. The blocks do resemble, at least superficially, landslides shed from the Hawaiian islands, particularly those north of Oahu-e.g., the Nuuanu landslide (Moore et al, 1989(Moore et al, , 1995Naka et al, 2000). However, there is no obvious source on the flank.…”
Section: Flankmentioning
confidence: 99%
“…The fluffy deposit was composed mostly of CaCO 3 (calcite) and amorphous iron, and high γ‐ray emission was observed in the same area (Hattori & Okano 1998). The low‐temperature vent (6.9°C) at the base of Loihi Seamount (4772 m deep), Hawaii, showed yellow patches (Naka et al . 2000).…”
Section: Resultsmentioning
confidence: 99%